Cross‐Neutralisation of the Neurotoxic Effects of Egyptian Cobra Venom with Commercial Tiger Snake Antivenom. (13th August 2012) - Kornhauser, Rachelle; Isbister, Geoffrey K.; O'Leary, Margaret A.; Mirtschin, Peter; Dunstan, Nathan; Hodgson, Wayne C.
Abstract Cross‐neutralisation has been demonstrated for haemorrhagic venoms including Echis spp. and Cerastes spp. and for Australia elapid procoagulant toxins. A previous study showed that commercial tiger snake antivenom (TSAV) was able to neutralise the systemic effects of the Egyptian cobra, Naja haje, in vivo but it is unclear if this was true cross‐neutralisation. The aim of the current study was to determine whether TSAV can neutralise the in vitro neurotoxic effects of N. haje venom. Both Notechis scutatus (10 μg/ml) and N. haje (10 μg/ml) venoms caused inhibition of indirect (supramaximal V, 0.1 Hz, 0.2 msec.) twitches of the chick biventer cervicis nerve–muscle preparation with t90 values (i.e. the time to produce 90% inhibition of the original twitch height) of 26 ± 1 min. (n = 4) and 36 ± 4 min.; (n = 4). This effect at 10 μg/ml was significantly attenuated by the prior addition of TSAV (5 U/ml). A comparison of the reverse‐phase HPLC profiles of both venoms showed some similarities with peak elution times, and SDS‐PAGE analysis elucidated comparable bands across both venoms. Further analysis using Western immunoblotting indicated TSAV was able to detect N. haje venom, and enzyme immunoassay showed that in‐house biotinylated polyclonal monovalent N. scutatus antibodies were able to detect N. haje venom. These findings demonstrate cross‐neutralisation between different and geographically separated snakes supporting potential immunological similarities in snake toxin groups for a large range of snakes. This provides more evidence that antivenoms could be developed against specific toxin groups to cover a large range of snakes.